Using novel scenario-based assessments to examine feasibility of integrating preventive nutrition services through the primary healthcare system in Bangladesh - Pramanik, Priyanjana; Nguyen, Phuong Hong; Avula, Rasmi; Billah, Sk. Masum; Ferdous, Tarana; Menon, Purnima (American Society for Nutrition, 2020)
Bangladesh's National Nutrition Services aims to deliver nutrition services to pregnant women and children through the primary health care system. Previous research highlighted gaps in coverage of preventive nutrition intervention delivery through this system but little is known about feasibility of reshaping service delivery to close the gaps. Prior to designing new approaches, we used a novel scenario-based feasibility testing approach to assess potential to strengthen service delivery.